Measuring the Capability to Raise Revenue: Process and Output Dimensions and Their Application to the Zambia Revenue Authority - Christian von Soest (German Institute of Global and Area Studies (GIGA), 2006)
The worldwide diffusion of the good governance agenda and new public management has triggered a renewed focus on state capability and, more specifically, on the capability to raise revenue in developing countries. However, the analytical tools for a comprehensive understanding of the capability to raise revenue remain underdeveloped. This article aims at filling this gap and presents a model consisting of the three process dimensions 'information collection and processing', 'merit orientation' and 'administrative accountability'. 'Revenue performance' constitutes the fourth capability dimension which assesses tax administration's output. This model is applied to the case of the Zambia Revenue Authority. The dimensions prove to be valuable not only for assessing the how much but also the how of collecting taxes. They can be a useful tool for future comparative analyses of tax administrations' capabilities in developing countries. – – Die weltweite Verbreitung der Good-Governance- und New-Public-Management- Konzepte hat zu einer zunehmenden Konzentration auf staatliche Leistungsfähigkeit und, im Besonderen, auf die Leistungsfähigkeit der Steuererhebung in Entwicklungsländern geführt. Allerdings bleiben die analytischen Werkzeuge für ein umfassendes Verständnis von Leistungsfähigkeit unterentwickelt. Dieser Artikel stellt hierfür ein Modell vor, das die drei Prozess-Dimensionen 'Sammeln und Verarbeiten von Informationen', 'Leistungsorientierung der Mitarbeiter' und 'Verantwortlichkeit der Verwaltung' beinhaltet. 'Einnahmeperformanz' ist die vierte Dimension und erfasst den Output der Steuerverwaltung. Das mehrdimensionale Modell wird für die Analyse der Leistungsfähigkeit der Steuerbehörde Zambias (Zambia Revenue Authority) genutzt. Es erweist sich nicht nur für die Untersuchung des Wieviel, sondern auch des Wie des Erhebens von Steuern als wertvoll. Die vier Dimensionen können in Zukunft zur umfassenden und vergleichenden Analyse der Leistungsfähigkeit verschiedener Steuerverwaltungen in Entwicklungsländern genutzt werden.
Keywords: 300; capability to raise revenue; revenue authority; tax administration; Zambia; Finanzverwaltung; Sambia